Analysis of The Impact of Job Training And Job Competence on Employee Productivity in Manufacturing Companies - Muhammad Syafri; Herry Syafrial; Maya Kasmita; Ni Luh Kardini; Shuarjana Mahayoga Bhandesa (Interdisciplinary Explorations in Research Journal, 2026)
Employee productivity is a critical determinant of operational efficiency, cost competitiveness, and long-term sustainability in the manufacturing sector. This study investigates the empirical impact of job training and job competence on employee productivity within manufacturing companies. Using a quantitative approach and a causal-associative research design, data were collected through structured questionnaires distributed to production-line employees selected via proportional stratified random sampling. The structural equation modeling (SEM) and multiple linear regression analyzes reveal that job training exerts a positive and significant influence on employee productivity by bridging skill gaps and reducing operational errors. Furthermore, job competence—comprising technical skills, behavioral traits, and explicit knowledge acts as a stronger predictor, significantly driving output quality and task efficiency. Simultaneously, both job training and job competence demonstrate a robust collective impact on productivity levels. These findings underline the strategic necessity for corporate human resource management to design continuous, high-impact training frameworks and refine competency-based recruitment systems. This study contributes to human resource management literature by validating the complementary mechanics of structured development programs and core professional capabilities in bolstering human capital performance within emerging market manufacturing ecosystems. Keywords: Job Training, Job Competence, Employee Productivity, Manufacturing Industry, Human Resource Management.